Odour mapping and air quality analysis of a wastewater treatment plant at a seaside tourist area - Luckert, Andreas; Aguado, Daniel; García-Bartual, Rafael; Lafita, Carlos; Montoya, Tatiana; Frank, Norbert (Environmental monitoring and assessment, 2023)
Although wastewater treatment plants (WWTPs) play a fundamental role in protecting the aquatic environment as they prevent organic matter, nutrients and other pollutants from reaching the natural ecosystems, near residential areas they can generate unpleasant smells and noise. The plant studied in the present work is in a seaside tourist area in the Valencian Community, Spain. The main aim was to detect any possible perceptible H2S concentrations from the WWTP by experimental measurement campaigns (including sensor readings and olfactometry measurements by two experts) plus mathematical modelling. After a thorough data analysis of the essential variables involved, such as wind speed, wind direction and H2S concentrations (the main odorant) and comparing their temporal patterns, it was found that the probability of affecting the residential area was highest from June to August before noon and in the late evening. The hourly H2S concentration, influent flow rate and temperature showed a positive correlation, the strongest (R2 = 0.89) being the relationship between the H2S concentration and influent flow rate. These two variables followed a similar daily pattern and indicated that H2S was emitted when influent wastewater was being pumped into the biological reactor. The H2S median concentration at the source of the emission was below 1393.865 μg/m3 (1 ppm), although concentrations 10 times higher were occasionally recorded. The observed H2S peak-to-mean ratio (1 min to 1 h of integration times) ranged from 1.15 to 16.03. This ratio and its attenuation with distance from the source depended on the atmospheric stability. Both H2S concentrations and variability were considerably reduced after submerging the inlet. The AERMOD modelling framework and applying the peak-to-mean ratio were used to map the peak H2S concentration and determine the best conditions to eliminate the unpleasant odour.
Veröffentlicht: 01. August 2023
Gesehen am 27.09.2023